As representações da cavalaria nos Romans de Chrétien de Troyes - Oliveira, Dyego Dias de (2017)
This dissertation research as representations of cavalry in Knightly Literature produced during the second half of the 12th century, with emphasis on the works of Chrétien de Troyes Arthurian circle. For that will analyze the first four works of this author: Eric and Enide, Cliges or that play death, Lancelot, the Knight of the cart and Yvain, the Knight of the lion. The goal is to investigate the representations conveyed by these narratives, comparing them together to identify the social function of these romans in knightly society of the 12th century. In this sense, from the analysis of the types of Knight presented by romans, consideration shall be given to the expressions of chivalry designed to better understand his own vision that aristocracy had about themselves or at least desperately craved disclose about themselves during the 12th century.